An ICT-based framework to improve global supply chain integration for final assembly SMES. Issue 5 (10th September 2018) - Cragg, Tony; McNamara, Tom
Abstract : Purpose: To access new markets and improve sourcing practices small to medium sized manufacturing companies (SMEs) increasingly seek suppliers and customers in distant countries. Yet these new relationships with global partners often pose problems of an agency nature. The purpose of this paper is to directly address these challenges through the proposal of an information and communication technology (ICT)-based framework. Design/methodology/approach: There has been very little research into how lead SMEs manage their global supply chains and the challenges they face. This paper uses a case study investigation to analyze how four French SMEs – final assemblers of machinery in the farming and agri-business sector – manage their international supply chains. Findings: It was observed that the relationships and interactions between the SMEs and their immediate upstream and downstream partners were dominated by the agency problem and fell into six distinct categories (termed "barriers" to effective supply integration), namely; asymmetries, contractual design, supplier dependence, product specifications, supply chain complexity and performance monitoring. Originality/value: The contribution of this paper is that a conceptual frame work was developed in which ICT solutions are offered to help address the barriers to supply chain integration, thus reducing the overall risk exposure due to externalities and problems of agency.